(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the results of a study of the level of awareness of educators and teachers of a specialized orphanage about the development of self-care skills in various fields of activity of children with severe mental retardation. The surveys, interviews and questionnaires have shown that the overwhelming majority (87.2%) of the interviewed specialists consider it important to form and develop the skills and abilities of self-care in children with severe mental retardation in a specialized orphanage. On the other hand, only 52.3% of interviewees believe that they have a sufficient level of awareness in the issues studied, 69.2% of the surveyed educators and teachers are not familiar in practice with the special methodological literature and the work experience of leading specialists about the development of self-care in this group of children. Therefore, in the practice of educating the skills and abilities of self-care skills in various fields of activity while working with children, the interviewed educators and special teachers rely on personal experience and knowledge, but not on modern methodological developments and the advanced experience of leading specialists. The results of this research made it possible to determine the main directions of organizational works for expanding the level and awareness, the acquisition of theoretical knowledge and practical skills and abilities by educators and teachers of a specialized orphanage 148 aimed at the formation and development of self-care skills of children with a severe mental retardation.